The utility of earth observation technologies in understanding impacts of land reform in the eastern region of Zimbabwe. Issue 4 (3rd July 2016) - Sibanda, Mbulisi; Dube, Timothy; Mubango, Tariro; Shoko, Cletah
ABSTRACT: Land tenure and land policies influence the spatial variations of land use/cover (LULC) at any given time or place. Thus, it is important to evaluate the role of land tenure policies on land cover changes. In this study, we evaluate the utility of Landsat Thematic Mapper (TM) images in understanding the impacts of the 2000 fast track land reform (FTLR) policy on LULC in the eastern region, Zimbabwe. Landsat images for the year 1995, 2000, 2005 and 2011 were classified using traditional image classification techniques (i.e. the maximum likelihood (ML) classifier) in a geographic information system (GIS) environment. Results indicate that forested areas drastically decreased by approx. 30% between the year 2000 and 2005 (during and after the FTLR), while croplands marginally increased by (approx. 30%) the results further showed that slight increase in bare lands (degraded lands) and disturbed lands. The observed LULC changes after FTLR were mostly induced by human activities resulting from changes in land tenure. Overall, the findings of this study underscores the importance of remotely sensed data in assessing the impact of FTLR on forest resources for purposes of informed and sustainable forest management.